Proceedings of the 2019 Conference of the International Fuzzy Systems Association and the European Society for Fuzzy Logic and 2019
DOI: 10.2991/eusflat-19.2019.68
|View full text |Cite
|
Sign up to set email alerts
|

Flexible bootstrap based on the canonical representation of fuzzy numbers

Abstract: A new resampling approach for simulating bootstrapped samples of fuzzy numbers is proposed. The secondary samples consist of fuzzy numbers which preserve the canonical representation (i.e., the value and ambiguity) of fuzzy numbers belonging to the primary sample, although may differ from the initial ones. This way the resulting bootstrap distribution has a richer support than obtained with the conventional method. Numerical experiments concerning two statistical tests for the expected value of a fuzzy random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…To avoid undesired repetitions which often appear in bootstrap Romaniuk and Hryniewicz [17][18][19] proposed a resampling method which enrich secondary samples with fuzzy observations imitating those from the primary sample but containing some incremental spreads on their 𝛼-cuts. Then Grzegorzewski et al [21,28] suggested another approach for generating bootstrap samples which may differ from the primary one but preserve the two-parameter canonical representation of each fuzzy observation, i.e., its value and ambiguity or the expected value and the width. We briefly discuss this method below, before introducing in Section 5 a new flexible bootstrap algorithm which preserves three-parameter canonical representation comprising the value, ambiguity and the fuzziness of a fuzzy number.…”
Section: Value-ambiguity (Va) Bootstrap Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…To avoid undesired repetitions which often appear in bootstrap Romaniuk and Hryniewicz [17][18][19] proposed a resampling method which enrich secondary samples with fuzzy observations imitating those from the primary sample but containing some incremental spreads on their 𝛼-cuts. Then Grzegorzewski et al [21,28] suggested another approach for generating bootstrap samples which may differ from the primary one but preserve the two-parameter canonical representation of each fuzzy observation, i.e., its value and ambiguity or the expected value and the width. We briefly discuss this method below, before introducing in Section 5 a new flexible bootstrap algorithm which preserves three-parameter canonical representation comprising the value, ambiguity and the fuzziness of a fuzzy number.…”
Section: Value-ambiguity (Va) Bootstrap Algorithmmentioning
confidence: 99%
“…for each i = 1, … , n, we draw randomly one triple from the set (21) and denoting it by (Val * , Amb * , Fuzz * ), we follow the consecutive transformations as in Section 4.2 which lead us to Eq. ( 16), where besides the given value Val * and the ambiguity Amb * one can find two unknown constants c and s. However, let us recall that there exist a one-to-one correspondence between s and the fuzziness of a fuzzy number, provided we restrict our attention to trapezoidal fuzzy numbers only.…”
Section: Value-ambiguity-fuzziness (Vaf) Bootstrap Algorithmmentioning
confidence: 99%
See 2 more Smart Citations